THE INFLUENCE OF PEER ENVIRONMENT ON STUDENT LEARNING ACHIEVEMENT MAJORING - Nur Indah Sari; Sitti Hajerah Hasyim; Fajriani Azis; Hariany Idris; H. Abd Rijal (Universitas Labuhanbatu, 2024)
This research aims to determine the influence of the peer environment on the learning achievement of students majoring in accounting at SMK Negeri 2 Sidrap. The variables in this research are the peer environment as the independent variable (X) and learning achievement as the dependent variable (Y). The population of this study were all students majoring in Accounting at Negen 2 Sidrap Vocational School, totaling 122 students, while the sample used proportionate stratified random sampling technique with a sample size of 55 students. The data collection technique used was a questionnaire and documentation. The data analysis technique used was descriptive analysis of the percentage of instrument tests and test the hypothesis using SPSS 25 for windows. Based on the results of the data analysis that has been carried out, a simple linear regression equation model Y-63.760+0.351 From the results of the analysis of the coefficient of determination (R), the value R2-45% is obtained, which means that the peer environment contributes to student learning achievement by 45% and the remaining 55% is influenced by natural factors. Meanwhile, from the results of the t-test, a significant value of 0.000 0.05 is obtained, which means Peer environment has a significant effect on student achievement, thus the 'accepted hypothesis.Keywords: Peer Environment; Learning Achievement